Artigos de opinião finalistas da Olimpíada de Língua Portuguesa “escrevendo o futuro”: um estudo do emprego dos articuladores e das sequências textuais - Teixeira, Gabriella Moura (2022)
This dissertation is part of the research line Text and speech in oral and written modalities, the Program of Post-graduate Studies in Portuguese Language, the Pontifical Catholic University of São Paulo, and has as its theme the study of articulators and textual sequences in finalists opinion articles of the Portuguese Language Olympiad "Writing the Future". The research questions that guide this study are: Which articulators and textual sequences are identified in opinion articles finalists of the 6th edition of the Portuguese Language Olympiad "Writing the Future"? What relations are established between articulators and text sequences in the aforementioned opinion articles? To answer these question, the general objective is to verify the relationship between articulators and textual sequences in finalists opinion articles of the 6th edition of the Portuguese Language Writing Future Olympics. The specific objectives are: 1) to identify, describe and analyze articulators and textual sequences present in the text plans of the selected opinion articles; 2) discuss the relations established between articulators and textual sequences that are interwoven in the composition of the text plans of the aforementioned opinion articles. In order to achieve these objectives, this study has as theoretical basis: Fávero and Koch (1998 [1983]), Koch (2020 [2004]) and Marcuschi (2008), which situate Textual Linguistics and its principles; Adam (2010, 2011, 2019) and Passeggi et al. (2010), dealing with Textual Analysis of the Discourses; Adam (2011, 2019), Marquesi, Elias e Cabral (2017), Marquesi et al. (2019) and Marquesi, Cabral and Rodrigues (2020), which address the concept of text plan; Adam (2011, 2019), Marquesi, Elias and Cabral (2017) and Marquesi et al. (2019), which deal with the textual sequences; and Koch (2011 [1987], 2018 [1989], 2020 [2004]) and Koch and Elias (2018), who discuss the textual articulators